Analysis of patients with vitiligo undergoing phototherapy in a referral hospital in the Federal District (Research, Society and Development, 2024)
Vitiligo is an acquired chronic disease of unknown etiology characterized by achromic patches on the body, which appear due to the progressive loss of melanocytes. Phototherapy is used as a treatment in cases when more than 20% of the body surface area is affected or after topical corticosteroid therapy has failed. The aim of this study was to evaluate the epidemiological profile of patients with vitiligo treated with phototherapy in a referral hospital in the Federal District and to assess the characteristics of this treatment. This is a descriptive, retrospective, case series study based on the analysis of medical records from 2012 to 2019. The study included 55 patients, 74.5% of whom were female and the majority aged between 31 and 40. All patients received UVB treatment twice a week, on non-consecutive days, starting with an initial dose of 200 mJ/cm². Of these, 30.9% experienced adverse effects, with erythema being the most common. Analyzing the epidemiological profile is important for making therapeutic decisions. This study suggests that more sessions, in young patients, may contribute to the success of repigmentation of the skin with vitiligo. However, further studies are necessary to generate other hypotheses regarding the variables that may affect the treatment of these patients.